(untitled) (Biological Sciences - PJSIR, 1994)
Nicardipine hydrochloride in bulk and in capsule dosage form has been assayed by two proposed independent analytical methods; (i) isocratic reverse-phase high-performance liquid chromatography (RP-HPLC) and (ii) differen- tial pulse polarography (DPP). The RP-HPLC involves employment of u-Bondapak-Ci , column of 300 x 3.9mm i.d. dimensions and mobile phase composed of 80% vtv CH3 CN +20% vIv (0.0 1M) CH3COONa buffer adjusted to pH 3.5 with glacial CH3COOH. The flow rate of the eluent was maintained at 1.5 ml/min. In the polarographic method, nicardipine produces a distinct reduction wave and a diffusion-controlled current which is linearly related to concentration ofnicardipine HCl over the range 10-100 g/ml. The RP-HPLC and DPP methods yielded comparable results when applied for the assay of nicardipine HCl in capsules (Pycarden®/30mg). However, the sensitivity and selectivity of the RP-HPLC can be improved substantially if the detection is carried out amperometrically.